Study of the incidence of tubal ligation and long-acting reversible contraceptives in tertiary care centre: a population-based study - Kausar, Shafiya; Ali, Mohammed Sharukh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Tubal ligation and long-acting reversible contraceptives (LARC) provide reliable long-term contraception; however, women’s choices are influenced by factors such as age, parity, previous deliveries, and counselling. This study aimed to assess and compare the acceptance of tubal ligation versus LARC among reproductive-aged women at a tertiary care centre, with the primary objective of identifying the demographic, obstetric, and socioeconomic factors affecting their choice of contraception. Methods: A prospective cross-sectional study was conducted from April 2023 to December 2024 at a tertiary care obstetrics and gynecology centre. Sexually active women aged 19-49 years seeking post-partum family planning were recruited via purposive sampling if opting for tubal ligation or LARC. Sociodemographic, obstetric, and contraceptive data were collected and analysed using SPSS. Results: Most participants were aged 26-32 years (79, 46.47%) and 18-25 years (75, 44.12%). FTND was the most common previous pregnancy (105, 61.76%). The uterus was anteverted in 165 (97.06%). Contraception choices included tubectomy (99, 58.23%), PPIUCD (28, 16.47%), and DMPA (34, 20%). LARC use was higher in P1L1 (28, 100%) and P1L1A2 (4, 100%), while tubectomy was associated with higher parity and previous LSCS (p<0.001). Delivery mode also influenced method (LSCS 37, 56.92%; FTND 62, 59.05%; p=0.0069). Conclusions: Tubal ligation was the main contraceptive choice, especially among multiparous women and those with prior cesarean sections. LARC was preferred by younger or lower-parity women but remained underutilised. Choices were influenced by obstetric history and delivery mode, underscoring the need for better counselling, awareness, and access.